Confederate combat commander : the remarkable life of Brigadier General Alfred Jefferson Vaughan Jr - Peterson, Lawrence K. (The University of Tennessee Press, 2013)
Known as one of the most aggressive Confederate officers in the Western Theater, Brigadier General Alfred Jefferson Vaughan Jr. is legendary for having had eight horses shot out from under him in battle-more than any other infantry commander, Union or Confederate. Yet despite the exceptional bravery demonstrated by his dubious feat, Vaughan remains a largely overlooked Civil War leader. In Confederate Combat Commander, Lawrence K. Peterson explores the life of this unheralded yet important rebel officer before, during, and after his military service. A graduate of Virginia M.